Rapid Tachyphylaxis of the Glucagon-Like Peptide 1–Induced Deceleration of Gastric Emptying in Humans - Nauck, Michael A.; Kemmeries, Guido; Holst, Jens J.; Meier, Juris J. (Diabetes (New York, N.Y.), 2011)
Glucagon-like peptide (GLP)-1 lowers postprandial glycemia primarily through inhibition of gastric emptying. We addressed whether the GLP-1-induced deceleration of gastric emptying is subject to rapid tachyphylaxis and if so, how this would alter postprandial glucose control. Nine healthy volunteers (25 ± 4 years old, BMI: 24.6 ± 4.7 kg/m(2)) were examined with intravenous infusion of GLP-1 (0.8 pmol · kg(-1) · min(-1)) or placebo over 8.5 h. Two liquid mixed meals were administered at a 4-h interval. Gastric emptying was determined, and blood samples were drawn frequently. GLP-1 decelerated gastric emptying significantly more after the first meal compared with the second meal (P = 0.01). This was associated with reductions in pancreatic polypeptide levels (marker of vagal activation) after the first but not the second meal (P < 0.05). With GLP-1, glucose concentrations declined after the first meal but increased after the second meal (P < 0.05). The GLP-1-induced reductions in postprandial insulin and C-peptide levels were stronger during the first meal course (P < 0.05). Likewise, glucagon levels were lowered by GLP-1 after the first meal but increased after the second test meal (P < 0.05). The GLP-1-induced delay in gastric emptying is subject to rapid tachyphylaxis at the level of vagal nervous activation. As a consequence, postprandial glucose control by GLP-1 is attenuated after its chronic administration.